KARDIOCHIRURGIA DOROSŁYCHDeterminants of perioperative anxiety and depression levels in professionally active men undergoing on-pump coronary artery bypass grafting - Krzych, Łukasz; Pawlak, Adam; Woźnica, Anna; Skarysz, Janusz; Eysymontt, Zbigniew; Krupka-Matuszczyk, Irena; Bochenek, Andrzej; Cisowski, Marek (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Aim: The study aimed to assess the relationship between perioperative anxiety and depression, and selected clinical parameters in men undergoing on-pump coronary artery bypass grafting (on-CABG). The project was designed as a pilot study aimed to estimate basic determinants then being investigated in a prospective manner. Material and Methods: We chose 120 professionally active males aged < 65 y.o. with coronary heart disease to participate in the study. After taking into account exclusion criteria, 50 men were involved and underwent on-CABG. The Polish version of the State-Trait (X1 and X2) Anxiety Inventory was used to assess the level of anxiety. The Beck Depression Inventory (BECK) was used to assess depression level. Results: State-anxiety was higher before the surgery (45.5 ± 9.1 vs. 38.4 ± 8.7; p = 0.004). Levels of anxiety and depression after on-CABG were correlated with baseline values: X1- r = 0.47 (p = 0.01), X2- r = 0.6 (p < 0.01), BECK- r = 0.7 (p < 0.01). Men with a history of previous myocardial infarction were more depressive before (4.7 ± 4.9 vs. 7.82 ± 3.4; p < 0.001) and after (12.5 ± 7.1 vs. 6.7 ± 5.7; p < 0.01) the surgery. Level of depression before on-CABG was correlated with ejection fraction (r = –0.49) and operative risk (r = 0.38÷0.47). Post-surgery depression was dependent on operative risk (r = 0.36÷0.71) and the number of grafts (R = 0.49). Post-operative anxiety was related to subjects’ age (r = 0.31÷0.32), operative risk (r = 0.36÷0.4), angina symptoms (R = 0.38), cardiopulmonary bypass time (r = 0.39) and the number of grafts (R = 0.63). Conclusions: Levels of anxiety and depression are lower a few days after on-CABG compared with values obtained before the surgery. Post-operative anxiety and depression positively correlate with baseline values. Determinants of pre-operative depression are: operative risk, previous myocardial infarction and low ejection fraction. Post-operative anxiety and depression are positively correlated with subjects’ age, angina symptoms and extent of the surgery.